Neighborly Surveillance: The Mississippi State Sovereignty Commission and the Development of a Post-Jim Crow Ideological Apparatus - Parsons, Ryan (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
The relations of production in Deep South regions like the Mississippi Delta require a high degree of control over race and class configurations. While the overt, de jure White supremacy that marked the post-Reconstruction era allowed for effective repression of dissent, the promise of federal intervention and grassroots organizing during the years of the civil rights movement required White elites to recalibrate methods of control. By integrating theories of racialization of space, internal colonialism, and Althusser’s (2006) notion of the ideological state apparatus, I suggest that this transition from overt to implicit control was accomplished by creating a culture of neighborly surveillance in which everyday Whites were deputized to surveil and report on civil rights organizing at the grassroots level. By neighborly surveillance, I refer to surveillance between and amongst private citizens enacted outside the purview of the formal state but in the interest of the powerful elite who control the state. I document this process through analysis of the archives of the Mississippi State Sovereignty Commission, an official state agency tasked with spying on and counteracting civil rights activity. These records demonstrate the extent to which non-state actors assumed the roles originally exercised by the de jure Jim Crow regime. Beyond augmenting understandings of the civil rights movement-era US South, this article contributes analytical insights to social and ideological transitions in other post-colonial, post-authoritarian spatial contexts.